Auditoría de gestión y sus efectos en el cumplimiento del presupuesto de la poblaciòn adulta mayor del MIES de la ciudad de Quevedo AÑO 2016 – 2017 - Yong Zambrano, Rudy Gabriela (2018)
The present investigation, analyse and assess the impact of the audit of management in the implementation of the budget of the priority needs of the older population of the Ministry of economic Inclusion and Social (MIES)., It is located in the parish on October 7, second street and C, of the city of Quevedo, Los Ríos province. It is noteworthy that, during the development of this project, employed several methods of research such as the descriptive, explanatory, deductive and inductive; same that allowed determine and substantiate if this institution fulfilled the goals set for the annual budget. Interview with the Director in charge, was also held to know how finance is manifesting the weaknesses and shortcomings of this institution in terms of the fiscal resource provided to them by the State and is also necessary to carry out audits of more management followed, also proceeded to make a sheet of internal control for the same and finally for data collection were also conducted surveys that were applied to public servants of the institution. According to the results of the tabulation, it was determined that the sample corresponded to 143 employees of MIES Quevedo, in which clear results were obtained about the budget received from the State, establishing that it only covers 80% of the needs of the Gerontological Center and that it was therefore necessary to improve the budgetary administration of the institution; Therefore, the suggestion was made to hold periodic and continuous meetings of the technical, administrative and financial area in order to reach a consensus in which the priorities regarding the budget are made known and efficiently handled so that the Next accounting period, the older adult population will be better served. Keywords: Management audit, annual budget, budget administration, Gerontologic Center, older adult.